A Missiological Analysis Of The Synergy Between The North Sulawesi Provincial Government And The Evangelical Church In Minahasa To Anticipate The Food Crisis Through Agriculture And Livestock Activities - Sarimbangun, Ramli; Kalalo, Jefry; Pinaria, Yeanly Wuena (Green Publisher Indonesia, 2024)
From a review of previous research on global reactions to food crises, most studies have focused on economic aspects. This review identified the following gaps: (1) There is no study discussing the synergy between the church and the government in addressing food crises; (2) No research is available on the role and social anticipation of communities in the context of food crises. This research is urgently needed because synergy between the government and the church is crucial in the context of food security in North Sulawesi. The objective of this research is to fill this research gap through a holistic and comprehensive approach to the synergy between the Provincial Government of North Sulawesi and the Evangelical Christian Church in Minahasa in anticipating the global food crisis by enhancing farming and livestock activities in North Sulawesi. The research method used is a descriptive qualitative design through content analysis combined with a missiology analysis approach of the church. Data collection was carried out using participatory observation, interviews, and literature studies. The novelty of this research includes: (1) The synergy between the Provincial Government of North Sulawesi and the Evangelical Christian Church in Minahasa in responding to and anticipating the global food crisis; (2) The combination of content analysis methods with church missiology analysis as a new approach. The output of this research is a conceptual framework and a strong missiological approach strategy in building and optimizing relevant and effective synergy.